Alto do Castelo's Iron Age occupation (Alpiarça, Portugal) - Arruda, Ana Margarida (2017)
Alto do Castelo, in Alpiarça (Portugal), is a site recognized by its close spatial relation with the Late Bronze Age necropolis of Tanchoal and Meijão. Although always connected with this moment of Protohistory, a Roman Republican occupation was also early assumed, based not only in a set of archaeological findings collected in the early xxth century and during the excavations directed by Ph. Kalb and M. Hock, but also by the identification of a wall and double ditch directly linked to this phase. However, Casa dos Patudos retains several Iron Age materials recovered during the fieldwork of the German Archaeological Institute team, and others found, in recent years, on the surface of the site. These Iron Age materials display characteristics that allow its association with the arrival and installation of the Mediterranean populations in the Tagus valley during the second half/late viiith century bc. This data makes possible to integrate Alto do Castelo in a dense network of Orientalized settlements discovered in the two banks of the Tagus river. The role played by these sites and their relations should be analyzed, taking into consideration the type of geographical disposition, the occupied areas, and of course, the archaeological materials.